Provenance of plumes in global convection models. (26th May 2015) - Hassan, Rakib; Flament, Nicolas; Gurnis, Michael; Bower, Dan J.; Müller, Dietmar
Abstract In global convection models constrained by plume motions and subduction history over the last 230 Myr, plumes emerge preferentially from the edges of thermochemical structures that resemble present‐day large low shear velocity provinces (LLSVPs) beneath Africa and the Pacific Ocean. It has been argued that large igneous provinces (LIPs) erupting since 200 Ma may originate from plumes that emerged from the edges of the LLSVPs and numerical models have been devised to validate this hypothesis. Although qualitative assessments that are broadly in agreement with this hypothesis have been derived from numerical models, a quantitative assessment has been lacking. We present a novel plume detection scheme and derive Monte Carlo‐based statistical correlations of model plume eruption sites and reconstructed LIP eruption sites. We show that models with a chemically anomalous lower mantle are highly correlated to reconstructed LIP eruption sites, whereas the confidence level obtained for a model with purely thermal plumes falls just short of 95%. A network of embayments separated by steep ridges form in the deep lower mantle in models with a chemically anomalous lower mantle. Plumes become anchored to the peaks of the chemical ridges and the network of ridges acts as a floating anchor, adjusting to slab push forces through time. The network of ridges imposes a characteristic separation between conduits that can extend into the interior of the thermochemical structures. This may explain the observed clustering of reconstructed LIP eruption sites that mostly but not exclusively occur around the present‐day LLSVPs.